Evaluation of post-extubation breathing pattern and indication of practices in a pediatric ICU - Ribeiro, Alessa; Souza, Michele (Brazilian Journal of Global Health, 2021)
OBJETIVO: Utilizar a Escala de Wood-Downes e o escore de desconforto alto proposto por de Downes & Raphaelly na avaliação do padrão respiratório e na indicação de dispositivos de suporte de oxigenação e/ou ventilatório após extubação orotraqueal. MÉTODOS: Trata-se de um estudo transversal, descritivo e quantitativo. O grupo foi composto pelos por 15 lactentes de 28 dias a 2 anos, internados na unidade de terapia intensiva pediátrica de agosto a outubro de 2018 e que estiveram dentro dos critérios de inclusão, seguindo os aspectos éticos da pesquisa. RESULTADOS: Dos 15 lactentes da amostra, 66,66% eram do sexo feminino. A média de idade foi de 6,4 e ±6,27 meses. O escore mais presente da escala de Wood-Downes no primeiro momento foi o moderado com em média 3,4 e ±1,91 passando para leve 1,6 e ±0,89 no segundo momento. O escore de desconforto alto no primeiro momento com média de 2,9 e ±1,62 diminuindo para 1,7 e ±0,79 no segundo momento. CONCLUSÃO: A utilização da escala de Wood-Downes e o escore de desconforto alto proposto por Downes & Raphaelly para avaliarmos o padrão respiratório no presente estudo, mostrou-se eficaz na indicação de suporte ventilatório não invasivo, devido ao score moderado ter sido o mais presente. Apesar do estudo não ter interferido na conduta médica acredita-se que as escalas utilizadas sejam ferramentas eficazes para o controle e avaliação da insuficiência respiratória aguda após a extubação dos lactentes. DESCRITORES: Ventilação Mecânica, Extubação, Pediatria, Fisioterapia. ABSTRACT OBJECTIVE: To employ the Wood-Downes Score and the upper airway obstruction score proposed by Downes and Raphaelly in the assessment of respiratory patterns and the indication of oxygen and ventilation support devices after orotracheal extubation. METHODS: It is a cross-sectional, descriptive, and quantitative study. The group was composed of 15 infants aged 28 days to 2 years old, hospitalized at the pediatric intensive care unit from august to october 2018, fulfilling the inclusion criteria and following the ethical in research aspects. RESULTS: Out of fifteen infants in the sample, 66,66% were female. The mean age was 6,4 ±6,27 months. The most common Wood-Downes score at baseline was moderate with mean 3,4 ±1,91, going to mild 1,6 ±0,89 at the second moment. The mean upper airway obstruction score at baseline was 2,9 ±1,62 decreasing to 1,7 ±0,79 at the second moment. CONCLUSION: The employment of the Wood-Downes Score and the upper airway obstruction score proposed by Downes and Raphaelly to assess the respiratory patterns in the present study, showed efficacy in the indication of non-invasive ventilatory support because the moderate score was the most present. Although the study did not interfere in the medical conduct, it is believed that the scores employed are useful tools to the control and assessment of the acute respiratory insufficiency after infant extubation. DESCRIPTORS: Mechanical ventilation, Extubation, Pediatrics, Physiotherapy.